Analysis Of Basic Land Facility Needs In Sape Port, Bima District, West Nusa Tenggara Province - Hendri Ginting; Sri Kartini; Paundu Wicaksono (Politeknik Transportasi Sungai Danau dan Penyeberangan Palembang, 2021)
The Sape Ferry Port is managed by PT ASDP FERRY (PERSERO) as a port operator that provides facilities to support operational activities at the Sape Ferry Port. Apart from the port of PT. ASDP Indonesia Ferry (Persero) is also a ship operator providing ferry boats serving the Sape - Labuan Bajo commercial route and the Sape - Waingapu Commercial route with 2 (two) ro-ro types of ferry units. However, the Sape Crossing Port still does there are basic landland facilities that are still lacking to non-existent, which can hinder port operations. Based on the results of the analysis, it can be seen that the Sape Crossing Port has not provided a deafroom that has an adequate area and seats for the waiting room so that many passengers sit on the floor while waiting for a ship whose trip is only once a day, there is no weigh bridge, and has a gangway that has not yet connected. to the deck of the ship so that the passengers and the vehicle still enter the same lane, namely the ship ramp door. Therefore, it is necessary to have a review and additions to some of the facilities that are lacking or even non-existent at the Port of Sape. This is done to improve the existing services at the Sape Ferry Port. Improvements to main land facilities, such as repairing the waiting room, adding weigh bridges, and adding a gangway that connects from the previous gangway to the ship's deck, were carried out to smoothen port operations so that passengers can experience the excellent service provided by the port.